2021
DOI: 10.7860/jcdr/2021/49172.15228
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Clinical Signs and Co-morbidities of Feeding Intolerance among Preterm Infants Aged 28-34 Weeks of Gestation in a Tertiary Care Hospital of Western Nepal- A Prospective Observational Study

Abstract: Introduction: Feeding intolerance is common among the preterm neonates and is associated with different co-morbidities like respiratory depression, respiratory distress syndrome, apnea, hyperbilirubinaemia, and hypoxic ischaemic encephalopathy. Aim: To find the incidence of feeding intolerance in preterm neonates from 28-34 weeks of gestation along with the clinical signs and co-morbidities associated with feeding intolerance. Materials and Methods: A prospective observational hospital based study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
2
3
1
Order By: Relevance
“… 7 The incidence of feeding intolerance also varied greatly in different studies done in different geographical areas, 4.2% in Dhaka, 36% in Bangladesh, 2.6% in Egypt, 34% in African Israelian and 15% in other Israelian, 11.02% in Western Nepal. 2 , 6 - 10 The prevalence of feeding intolerance in this study was found to be 38.18% which is almost similar to a study done in Bangladesh, 8 but higher than another Bangladeshi study. 2 Here, the majority of preterm with feeding intolerance had features of, abdominal distension (47.6%) and some had apnea (23.8%), gastric residual 14.3%, and vomiting (14.3%).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“… 7 The incidence of feeding intolerance also varied greatly in different studies done in different geographical areas, 4.2% in Dhaka, 36% in Bangladesh, 2.6% in Egypt, 34% in African Israelian and 15% in other Israelian, 11.02% in Western Nepal. 2 , 6 - 10 The prevalence of feeding intolerance in this study was found to be 38.18% which is almost similar to a study done in Bangladesh, 8 but higher than another Bangladeshi study. 2 Here, the majority of preterm with feeding intolerance had features of, abdominal distension (47.6%) and some had apnea (23.8%), gastric residual 14.3%, and vomiting (14.3%).…”
Section: Discussionsupporting
confidence: 85%
“…Free Full Text Articles are Available at www.jnma.com.np Israelian, 11.02% in Western Nepal. 2,[6][7][8][9][10] The prevalence of feeding intolerance in this study was found to be 38.18% which is almost similar to a study done in Bangladesh, 8 but higher than another Bangladeshi study. 2 Here, the majority of preterm with feeding intolerance had features of, abdominal distension (47.6%) and some had apnea (23.8%), gastric residual 14.3%, and vomiting (14.3%).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations